2017
DOI: 10.5098/hmt.9.25
|View full text |Cite
|
Sign up to set email alerts
|

MHD Maxwell Fluid Flow in Presence of Nano-Particle Through a Vertical Porous-Plate With Heat-Generation, Radiation Absorption and Chemical Reaction

Abstract: Present study concerns with the numerical investigation of MHD transient naturally convective and higher order chemically reactive Maxwell fluid with Nano-particle flow through a vertical porous plate with the effects of heat generation and radiation absorption. A boundary layer approximation is carried out to develop a flow model representing time dependent momentum, energy, and concentration equations. The governing model equations in partial differential equations (PDEs) form are transformed into a set of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Seth et al, (2017) examined that effect of hall current on MHD natural convection heat and mass transfer flow of rotating fluid past a vertical plate with ramped wall temperature. Arifuzzaman et al (2017) analyzed that MHD maxwell fluid flow in presence of nano-particle through a vertical porous-plate with heat-generation, radiation absorption and chemical reaction. Yongbin Zhang (2017) has been reported that an influence of pore wall surface property on flux of cylindrical-shaped nanoporous filtering membrane.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Seth et al, (2017) examined that effect of hall current on MHD natural convection heat and mass transfer flow of rotating fluid past a vertical plate with ramped wall temperature. Arifuzzaman et al (2017) analyzed that MHD maxwell fluid flow in presence of nano-particle through a vertical porous-plate with heat-generation, radiation absorption and chemical reaction. Yongbin Zhang (2017) has been reported that an influence of pore wall surface property on flux of cylindrical-shaped nanoporous filtering membrane.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Rajput and Gaurav 2 explored the Soret result on non-time dependent MHD flow by using an impulsively begun inclined wavering plate with the effect of variable temperature. In the occurrence of nanoparticles, Arifuzzaman et al 3 analyzed the MHD Maxwell fluid flow on a perpendicular porous plate along with radiation absorption, chemical reaction and heat generation. Hosseinzadeh et al 4 thought that the possessions of nonlinear radiation and reactive chemical flow on the Maxwell fluid across a porous media equipped with a convectively heated plate are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Biswas et al examined the character of hydromagnetic nanofluid explicitly on a perpendicular stretched sheet/plate with radiation absorption [34]. Arifuzzaman et al and Rabbi et al analysed the character of different fluids flow by using EFDM over porous plate [35][36][37][39][40][41][42]. A similar method is applied by Biswas et al to observe the 2D transient optically dense Grey nanofluid impact of periodic magnetic field [38].…”
Section: Introductionmentioning
confidence: 99%